(untitled) (American Journal of Islam and Society, 2008)
One of the paradoxes facing conservative Muslims in North America is that while their apologetic literature stresses “Islam as justice” – that justice is the paradigmatic Qur’anic virtue after piety – in the eyes of the general public the progressive Muslims have claimed the mantle of justice. This is a shame, since conservative or traditionalMuslims are held to be generally unjust, whereas, as followers of Islam’s traditional teachings, they ought to be at the forefront of the struggle for social and economic justice. There are two dimensions to this perception: one is externally generated and constitutes a very real threat to NorthAmerica’sMuslims; the second one is internally generated and constitutes a significant barrier to Islam’s positive reception by NorthAmerican society. It is not an original statement to note that Islam’s general public image is bad. Many scholars, among them Edward Said, Karim Karim, and Jack Shaheen, have demonstrated time and again how the western legacy of Orientalism moved out of the academy and into the secular media with the rise of the film and print media industries. Such post-9/11 experts as Mahmoud Hamdani have noted the refining of this image into a “good Muslim”/“bad Muslim” dichotomy. The secular or “moderate” Muslims receive the accolade of the “good Muslims,” while traditional and conservativeMuslims are the “badMuslims.” Efforts by Daniel Pipes and other neoconservative writers to ensure that the general public and policy makers do not distinguish between moderate conservatives and those who endorse violence to achieve their goals have, unfortunately, been very successful. The Clarion Fund’s mass mailing of the DVD “Radical Obsession” to 28 million households in September 2008 clarifies the enormous power behind such neoconservative goals. “Radical Obsession,” which purports to be only about jihadism, manages through its imagery to connect allMuslims to violence.An excellently executed piece of propaganda, it will likely have the desired goal: creating fear in the general public’s mind about conservative Muslims. (Secular and progressive Muslims will also suffer in the long run, as the general public will not be able to distinguish between a secular and a non-secular Muslim, which is why the support voiced by some of these Muslims vis-à-vis the DVD is disappointing, to say the least.) ...